Interleukin-18 in lupus nephritis: a meta-analysis of cytokine signaling dysregulation in immune-mediated nephropathy - Zhou, Cheng; Li, Jiayi; Zhao, Jing; Bai, Xue-Yuan; Shang, Shunlai; Li, Wenge (Frontiers in Immunology, 2025)
BackgroundLupus nephritis (LN), the most severe renal complication in systemic lupus erythematosus (SLE), features inflammatory cascades from dysregulated cytokine networks. Although IL-18 (a pyroptosis effector) critically contributes to kidney inflammation, its dynamic changes across LN renal pathological stages and clinical correlations require systematic investigation. This meta-analysis explores peripheral blood IL-18’s association with renal pathological damage in LN, providing molecular insights into inflammatory signaling network imbalances.Study design and methodsThis meta-analysis was performed to quantitatively assess the relationship between circulating IL-18 levels and lupus nephritis (LN) in SLE patients, incorporating stratified analyses by renal histopathological classifications (WHO classes II, III, IV, and V) to evaluate disease progression markers. We systematically queried multiple biomedical databases including PubMed, Embase, Scopus, Web of Science Core Collection, Wiley Online Library, MEDLINE, and Cochrane Library, encompassing all articles published before July 10, 2025. We pooled computed standardized mean difference (SMD) and its 95% confidence interval for meta-analytical using STATA 18.0.ResultsA total of 18 eligible studies were included, 1,033 SLE with LN, 537 SLE without LN, and 1,083 matched healthy controls. The analysis results displayed that LN patients showed a significantly higher level of circulating IL-18 level in comparison with healthy controls (SMD = 2.51, 95% CI [1.91-3.12];I2 = 96.2%, p=0.000). The conclusion was equally applicable in subgroups divided based on sample type, mean age, disease duration, and testing method. SLE with LN patients showed a significantly higher level of circulating IL-18 level than SLE without LN(SMD = 1.53 95% CI [0.87–2.20]; I² = 95.7%, p =0.000). Compared with other classifications of LN, IV-LN patients demonstrate the highest serum IL-18 levels.ConclusionsThis study reveals elevated IL-18 in LN patients, establishing it as a risk biomarker for SLE renal injury. The findings provide molecular evidence for IL-18 signaling imbalance in kidney inflammation and highlight therapeutic potential in targeting IL-18 to combat LN progression.